International Handbook of Career Guidance - Athanasou, James A.; van Esbroeck, R. (Springer Netherlands : Imprint: Springer, 2008)
The International Handbook of Career Guidance represents a project of inter- tional professional cooperation. It is intended as a catalyst for reform and was designed to support the development of career guidance in the years to come. Working for over four years from Belgium and Australia we had the privilege to collaborate with over 50 colleagues throughout the world to produce this Handbook. In every instance we selected key researchers who have an established reputation in the field of career development. They agreed to be involved and we are grateful for their support in this major effort. In this handbook we have tried to bring together a collection that summarises the diverse aspects of career guidance. It is a synthesis of the domain of career and vo- tional guidance firstly for an international readership and secondly it is designed to act as a reference for academics, researchers and professionals in the expanding field of career development. For this reason the Handbook includes coverage of the ba- ground and history of guidance right through to poignant issues relating to careers in the modern world of work. Policy issues relating to the provision of careers services as well as professional issues relating to career education, career counselling, career assessment, program evaluation and research methodologies are covered.